Haemorrheological abnormalities in unstable angina pectoris: a relation independent of risk factor profile and angiographic severity. Issue 6 (December 1989) - Neumann, F J; Tillmanns, H; Roebruck, P; Zimmermann, R; Haupt, H M; Kübler, W
Abstract : Plasma viscosity, photometric erythrocyte aggregation index, and erythrocyte filterability were measured in 194 patients with coronary artery disease. Patients with unstable angina (n = 64) had a higher plasma viscosity and photometric erythrocyte aggregation index than patients with stable angina (95% confidence intervals for the mean difference: 0.052-0.100 mPa.s for plasma viscosity, and 43%-72% for the photometric erythrocyte aggregation index). Multiple regression with fibrinogen, cholesterol, high density lipoprotein cholesterol, triglycerides, blood pressure, smoking habits, coronary artery score, and left ventricular ejection fraction as independent variables showed a significant partial correlation between fibrinogen and the photometric erythrocyte aggregation index (r2 = 0.20) and plasma viscosity (r2 = 0.09), between triglycerides and plasma viscosity (r2 = 0.05), and between aortic pressure and erythrocyte filterability (r2 = 0.03). Logistic regression for unstable/stable angina with the haemorrheological variables as independent variables correctly identified 72% of the patients with stable angina and 78% of those with unstable angina. Inclusion of all the variables investigated did not substantially improve the discriminative potential of the logistic regression model. Unstable angina is associated with an impairment of blood fluidity that is essentially independent of risk factor profile and angiographic data.